THE ROLE OF ISLAMIC LEARNING ASSEMBLY IN DEVELOPING THE PROSPEROUS FAMILY; A Case Study of Islamic Learning Assembly in Medan City - Syukri Syukri; Sulaiman Muhammad Amir (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
The aim of this study is to find out the role of learning assemblies in coaching happy families in Medan and surrounding areas. The point is to contribute thoughts to the Medan City Government, administrators, Islamic communities and the community in realizing a happy, affection and grace families in Medan City. The results of this study is that an educational institution for people who grow and develop from the Islamic community of the city of Medan itself, whose interests are for the benefit of Muslims. So, Learning Assemblies is a non-governmental organization (NGO) in Medan City whose life is based on mutual help and love among them. In addition, the Learning Assemblies of Medan City has a very important role in coaching happy families, especially in realizing religious functions, realizing family education, economic function and family welfare, fostering harmonization of husband and wife and fostering harmonious relations between family members, communities and the Government of Medan city.Keywords: Assembly, Learning, Family, Happy, Medan City